2008
DOI: 10.3177/jnsv.54.89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea on Volatile Sulfur Compounds in Mouth Air

Abstract: Summary Many food products are claimed to be effective in controlling halitosis. Halitosis is caused mainly by volatile sulfur compounds (VSCs) such as H 2 S and CH 3 SH produced in the oral cavity. Oral microorganisms degrade proteinaceous substrates to cysteine and methionine, which are then converted to VSCs. Most treatments for halitosis focus on controlling the number of microorganisms in the oral cavity. Since tea polyphenols have been shown to have antimicrobial and deodorant effects, we have investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 26 publications
1
68
0
4
Order By: Relevance
“…H 2 S had the lowest score, which was 0.27 ± 0.39 ng/10 ml for PS group and 0.33 ± 0.34 ng/10 ml for EOS group. This showed that oral malodor may arise if there is no oral activity done in 4 hrs [12]. That condition was proved by the mean of CH 3 SH >0.5 ng/10 ml and the mean of (CH 3 ) 2 S >0.2 ng/10 ml, which is the threshold by which an odor can be smelled by the human sense of smell, according to Tonzetich criteria.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…H 2 S had the lowest score, which was 0.27 ± 0.39 ng/10 ml for PS group and 0.33 ± 0.34 ng/10 ml for EOS group. This showed that oral malodor may arise if there is no oral activity done in 4 hrs [12]. That condition was proved by the mean of CH 3 SH >0.5 ng/10 ml and the mean of (CH 3 ) 2 S >0.2 ng/10 ml, which is the threshold by which an odor can be smelled by the human sense of smell, according to Tonzetich criteria.…”
Section: Discussionmentioning
confidence: 96%
“…This was consistent with the Acceptance Program Guideline released by the American Dental Association at the Council on Scientific Affairs 2003. According to Tonzetich, the effect from oral activity will disappear in 3 hrs [12]. Following the initial measurement of oral malodor parameters, participants were requested to consume one type of oral refresher strip (randomized as either EOS or PS).…”
Section: Research Articlementioning
confidence: 99%
“…9). Differences in subgingival microbiota among individuals are caused by various physical and chemical characteristics of the oral environment, such as temperature, oxygen tension and availability of nutrients (24). Most oral bacteria are grown in a neutral environment (pH equal to 7).…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported that using green tea mouthwash significantly reduces the volatile sulfur components level in patients with gingivitis [13]. Another study has demonstrated that green tea extract had the ability to remove odorant sulfur [14].…”
Section: Green Tea and Halitosismentioning
confidence: 99%